(untitled) (Research, Society and Development, 2021)
Allelopathic activity study has been used to combat and control diseases, insects and weeds. This work aimed to evaluate the allelopathic effect of extracts from caju-de-árvore-do-cerrado (Anacardium othonianum) leaves on germination and initial growth of lettuce (Lactuca sativa L.) and radish (Raphanus sativus L.) seedlings. Initially, aqueous extracts from in natura leaves were obtained by two methods of aqueous extraction: infusion and decoction. The lettuce and radish germination and growth bioassays were carried out in triplicate, with treatments consisting of six different dilutions of the extracts, analyzing the germination percentage, root length and seedlings aerial-part length after 7 days of incubation, under artificial temperature and light conditions. The allelopathic potential was verified in both extracts of caju-de-árvore-do-cerrado leaves, due to the sensitivity observed in the lettuce and radish seeds. In addition, it was observed that the effects of allelochemicals are dependent on the dosage, since variations in allelopathic effects (inhibitory and/ or stimulating) were observed when changing the concentration of the extracts applied.